Early and sustained improvement with vilazodone in adult patients with major depressive disorder: post hoc analyses of two phase III trials. (February 2014) - Jain, Rakesh; Chen, Dalei; Edwards, John; Mathews, Maju
Abstract Objective: To retrospectively examine the timing of depressive symptom improvement in patients treated with vilazodone, a selective serotonin reuptake inhibitor (SSRI) and 5-HT1A partial agonist. Research design and methods: Post hoc analyses were conducted on pooled data from two phase III, multicenter, 8 week, double-blind, randomized, controlled trials (RCTs) of vilazodone 40 mg/day or placebo in adult patients with major depressive disorder (MDD). Clinical trial registration: Randomized controlled trial 1: ClinicalTrials.gov identifier: NCT00285376, http://ClinicalTrials.gov/ct2/show/NCT00285376; randomized controlled trial 2: ClinicalTrials.gov identifier: NCT00683592, http://ClinicalTrials.gov/ct2/show/NCT00683592. Main outcome measures: Montgomery–Åsberg Depression Rating Scale (MADRS) total score least squares (LS) mean change from baseline to Week 8; MADRS single items LS mean change from baseline; MADRS responder analyses: response = ≥50% reduction in baseline score; cumulative response = proportion of patients at each assessment who achieved response that was sustained at all subsequent weeks; sustained response = ≥50% reduction in baseline MADRS total score at last two visits; and sustained response plus MADRS score ≤12 at the last two visits of the study. Results: LS mean difference (LSMD) and 95% confidence interval (95% CI) for change from baseline to Week 8 was significantly greater in favor of vilazodone versus placebo (−2.8 [−4.1 to −1.4]; p < 0.0001); differences between vilazodone and placebo were statistically significant beginning at Week 1. Early improvement in depressive symptoms was suggested by statistically significant separation from placebo on seven of ten MADRS single items as early as Week 1 or Week 2. A significantly greater proportion of vilazodone patients achieved response using all responder criteria, with early and sustained improvement consistently observed. Conclusions: Early and sustained improvement of depressive symptoms was retrospectively observed in patients treated with vilazodone; early findings may be related to overall treatment outcomes.